2015
DOI: 10.4103/2277-9175.170677
|View full text |Cite
|
Sign up to set email alerts
|

Methylation pattern of ALX4 gene promoter as a potential biomarker for blood-based early detection of colorectal cancer

Abstract: Background:To develop a non-invasive screening method for colorectal cancer, we evaluated the methylation of ALX4 gene promoter in serum samples from patients with colorectal cancer (CRC) and equal number of healthy individuals.Materials and Methods:In serum samples from 25 patients with colorectal cancer and 25 healthy control subjects, isolated serum free-floating DNA was treated with sodium bisulfite and analyzed by methylation-specific polymerase chain reaction (MSP) with primers specific for methylated or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Homeobox protein aristaless-like (ALX4) is a homeodomain transcription factor associated with bone, skin, and hair follicle development [ 182 , 183 ]. It has been reported that there was a significant difference of ALX4 methylation status between a sample of Iranian colorectal cancer patients and controls which introduced that as an efficient marker for the early detection of colorectal cancer in this population [ 62 ]. Similarly, ALX4 methylation was observed among German patients with colorectal, esophageal, and gastric cancers [ 184 ].…”
Section: Developmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Homeobox protein aristaless-like (ALX4) is a homeodomain transcription factor associated with bone, skin, and hair follicle development [ 182 , 183 ]. It has been reported that there was a significant difference of ALX4 methylation status between a sample of Iranian colorectal cancer patients and controls which introduced that as an efficient marker for the early detection of colorectal cancer in this population [ 62 ]. Similarly, ALX4 methylation was observed among German patients with colorectal, esophageal, and gastric cancers [ 184 ].…”
Section: Developmental Factorsmentioning
confidence: 99%
“… Yari [ 61 ] developmental factors ALX4 2015 Colorectal 25 patients 25 controls Serum Hyper methylation. Salehi [ 62 ] PAX5 2018 Gastric 35 patients 35 controls Blood Hyper methylation. Haghverdi [ 63 ] MiR-129-2 2019 Gastric 50 N/T Tissue Hyper methylation.…”
Section: Introductionmentioning
confidence: 99%
“…Tests like Epi proColon show great clinical potential because patients already prefer these non-invasive tests over colonoscopy/sigmoidoscopy for screening, and SEPT9 methylation is superior at detecting early stage disease over other non-invasive tests like fecal occult blood testing [ 100 , 101 , 102 ]. Combinations of other hypermethylated genes as stool or blood biomarkers have not displayed the high sensitivity observed in the SEPT9 methylation assays [ 89 , 103 ].…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%
“…Aberrant CpG island methylation of the promoter region of p16 and IGFBP7 bypasses this dormant state and drives MVHPs further to sessile serrated adenomas (SSAs) [ 97 ]. In blood samples, hypermethylated ALX4 [ 80 , 98 ], NEUROG1 [ 99 ], APC [ 100 ], 6-O-Methylguanine-DNA Methyltransferase (MGMT) [ 101 ], MLH1 [ 82 ], HLTF [ 102 ], Ras association domain family member 2 (RASSF2A) [ 101 ], Syndecan 2 (SDC2) [ 103 ], SEPT9, Preprotachykinin-1 (TAC1) [ 104 ] and WIF1 [ 101 ] were detected in early stage CRC; hypermethylated HPP1, HLTF, secreted Frizzled Related Protein 2 (SFRP2) [ 105 ], VIM [ 106 ], tissue factor pathway inhibitor 2 (TFPI2) [ 107 , 108 ] and p16 [ 89 ] were found positively correlated with distant tumor metastasis; hypermethylated ALX4, fibrillin-2 (FBN2), HPP1 (Alias TMEFF2) [ 102 ], HLTF [ 83 ], p16 [ 91 ], TMEFF1 [ 102 ] and VIM [ 99 ] were associated with poor prognosis; and hypermethylated HLTF [ 109 ], HPP1 [ 109 ], runt- related transcription factor 3 (RUNX3) [ 110 ], p16 [ 91 ] and TFPI2 [ 107 , 108 ] were associated with CRC recurrence. It is conceivable that a robust biomarker panel of methylated genes will be developed into a clinically accurate CRC screening method in the future, and the development of blood-based biomarkers should improve patient compliance and the detection of CRC at early stage.…”
Section: Line-1mentioning
confidence: 99%